Synthesis of Al/TiC–Al2O3 nanocomposite by mechanical alloying and subsequent heat treatment. Issue 7 (15th May 2016) - Mehrizi, M. Zarezadeh; Beygi, R.; Eisaabadi, Gh.
Abstract: In this study, Al/TiC–Al2 O3 nanocomposite was synthesized via mechanical alloying and heat treatment. Phase development and structural changes were studied by X-ray diffraction technique and field-emission gun scanning electron microscopy. The results showed that the phase evolutions during mechanical alloying were strongly dependent on milling time until 20 h by formation of Al3 Ti and Al2 O3 . After that, by increasing milling time, no new phases formed. Heat treatment of 60 h milled powder showed that no new phases (especially TiC) were found after annealing at 500 °C. But increasing temperature to 1000 °C caused the Al3 Ti and TiO2 peaks disappeared and TiC peaks emerged. These results confirmed that the formation of TiC is not feasible in an Al–TiO2 –C system with excess Al by mechanical alloying.